Migration for Development: From Challenges to Opportunities - Klaus F. Zimmermann (Global Labor Organization (GLO), 2017)
This contribution investigates the opportunities of migration for developing countries. The benefits of migration for sending countries are often undervalued. But migrants may foster trade, remittances, innovations, investments back home, and even return home at some time with better human capital. Functioning diasporas can lead to stable factors of development. Policies in receiving developed countries towards migrants can enhance the positive impact of migration for development. Among those are measures to support the early integration of migrants into the educational systems and in the labor markets, including jobs for asylees. Dual citizenships and circular migration contracts are possible instruments. Migration policy can be an effective development policy.
Keywords: F22; F24; F66; J61; O15; 330; Remittances; circular migration; social remittances; diaspora economics; development; refugees; forced migration; dual citizenships; jobs for development; brain drain; brain gain